2005
DOI: 10.1126/science.1113523
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Supercurrent Through Semiconductor Nanowires

Abstract: Nanoscale superconductor/semiconductor hybrid devices are assembled from indium arsenide semiconductor nanowires individually contacted by aluminum-based superconductor electrodes. Below 1 kelvin, the high transparency of the contacts gives rise to proximity-induced superconductivity. The nanowires form superconducting weak links operating as mesoscopic Josephson junctions with electrically tunable coupling. The supercurrent can be switched on/off by a gate voltage acting on the electron density in the nanowir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
548
3
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 491 publications
(584 citation statements)
references
References 28 publications
31
548
3
2
Order By: Relevance
“…Josephson junctions and coherent quantum transport have been attracting interest in recent years due to the development of modern nanofabrication techniques, which enable the fabrication of nanoscale hybrid superconducting devices in a broad range of design and materials. Josephson junctions realized with semiconductor nanowires (NWs) [4][5][6][7][8][9][10] have shown a high potential in different types of nanoscale devices demonstrating, for example, tunable supercurrents [5,6], the supercurrent reversal [8], and the suppression of supercurrent by hot electron injection [10]. NWs have also been used for superconducting quantum interference devices (SQUIDs) [8] and tunable Cooper pair splitters [11].…”
Section: Introductionmentioning
confidence: 99%
“…Josephson junctions and coherent quantum transport have been attracting interest in recent years due to the development of modern nanofabrication techniques, which enable the fabrication of nanoscale hybrid superconducting devices in a broad range of design and materials. Josephson junctions realized with semiconductor nanowires (NWs) [4][5][6][7][8][9][10] have shown a high potential in different types of nanoscale devices demonstrating, for example, tunable supercurrents [5,6], the supercurrent reversal [8], and the suppression of supercurrent by hot electron injection [10]. NWs have also been used for superconducting quantum interference devices (SQUIDs) [8] and tunable Cooper pair splitters [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in techniques for fabrication of quantum dot systems have made it possible to produce S-QD-S systems [3][4][5][6][7] enabling experimental studies of this intriguing interplay. In carbon nanotubes [3], it was found that the Kondo state persists when the energy needed for breaking the Cooper pairs is compensated by the energy gained in forming the Kondo state (T K > ).…”
mentioning
confidence: 99%
“…Th ey also rapidly exclude materials forming near the growing walls, terminating propagation through the crystal. Th e LED, which is a forward-biased junction of a p-type (hole-transporting) and n-type (electron-transporting) material, can be downsized by the use of 1D NWs and also benefi t, in effi ciency, from the superior electronic [2][3][4] and thermal [5] transport properties compared with their bulk counterparts. One of the challenges is doping the NWs, and the other is, of course, achieving a good electrical p-n junction.…”
Section: Solid-state Lighting and Ledsmentioning
confidence: 99%